Factors affecting outdoor physical activity (OPA) in children and adolescents: A systematic review and meta-analysis - Jinghui Deng; Tong Liu; Zhengyin Long (Heliyon)
Aim: The outdoor physical activity (OPA) of children and adolescents in the ''Z'' era decreased sharply compared with the previous generation, and the purpose of this study is to explore the factors that influence children and adolescents’ participation in OPA. Method: For this systematic review and meta-analysis, we searched Eric, PsycArtical, PsycINFO, Pubmed, Pubmed, Medline, SCOPUS, Web of Science Core Collection, CNKI, and the search ending date was March 20, 2024.The quality of the evidence was assessed with the crosssectional study tool (Appraisal tool for Cro-SS-Sectional Studies, AXIS).Employing meta-analysis to evaluate the strength of evidence for the influencing factors. Results: Results show that, in the dimension of basic demographic characteristics, parents' educational level and family income are significant factors affecting children and adolescents' participation in OPA. In the dimension of family characteristics, parents' attitudes towards their children and adolescents' participation in OPA, as well as their encouragement and support, are significant factors influencing participation, but the factor of parents' attitudes is unstable. In the dimension of perceived social environment, perceived community cohesion, community safety, and peer support are significant factors affecting children and adolescents’ participation in OPA, but the factors of community safety and peer support are unstable. In the dimension of the physical environment, access to activity facilities is the only significant influencing factor. Suggestion: The factors affecting the participation of children and adolescents in OPA are relatively complex. It is suggested to consider building child-friendly communities from many aspects to increase OPA for children and adolescents to enhance their physical health and mental health.